Kerusakan dan Kerugian Akibat Serangan Lalat Buah (Diptera: Tephritidae) pada Pertanaman Jeruk - WIJAYA, I NYOMAN; ADIARTAYASA, WAYAN; DWIPANANDA, I GEDE BAGUS (Agrotrop : Journal on Agriculture Science, 2018)
Damage and Product Losses by Fruit Flies Bactrocera dorsalis Complex (Diptera: Tephritidae) at Citrus Cultivation. This research knows the damage and nominal loss caused by fruit flies attack on citrus cultivation. The study took place from May to September 2016, from fruit to harvest, fruit fly observations were performed using relative methods. The results showed the damage of fruit at citrus cultivation in place of research have category relative moderate until heavy. Of the 10 plant samples observed 3 damaged plants reached 51%. Then 7 other plant samples suffered damage in the medium category. But the average damage reached 44%, this is a fruit fly is categorized as a very harmful pest. Nominal losses in 10 sample plants observed with the number of fruit fell as much as 943 fruit and fruit weight reached 157.17 kg obtained nominal loss of Rp. 471,500. Based on the data obtained hectar loss of Rp.29.468.750. Fruit fly attacks have increased along with the condition of citrus fruits that begin to experience physiological development so that the loss of the number of fruit fall that resulted in economic losses.